Lubelska komisja Boni Ordinis i jej wpływ na rozwój przestrzenny miasta - Przesmycka, Natalia; Przesmycki, Jerzy (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
The activity of the Lublin Good Order Committee (Boni Ordinis) was the first that gave measurable results to the action of improvement of the image of city, its administration and regulation issues. The city was destroyed and in economic collapse after the seventeenth century wars. Other activities of the Commission of Boni Ordinis was also a manifestation of social thought and increase of the importance of the middle class in the country.